A T-type method for characterization of the thermoelectric performance of an individual free-standing single crystal Bi2S3 nanowire. Issue 5 (13th January 2016) - Ma, Weigang; Miao, Tingting; Zhang, Xing; Takahashi, Koji; Ikuta, Tatsuya; Zhang, Boping; Ge, Zhenhua
Abstract : A comprehensive T-type method is developed to evaluate the thermoelectric performance of one-dimensional nanostructures and an individual Bi2 S3 nanowire is studied. Abstract : A comprehensive method to evaluate the thermoelectric performance of one-dimensional nanostructures, called the T-type method, has been first developed. The thermoelectric properties, including the Seebeck coefficient, thermal conductivity and electrical conductivity, of an individual free-standing single crystal Bi2 S3 nanowire have been first characterized by applying the T-type method. The determined figure of merit is far less than the reported values of nanostructured bulk Bi2 S3 samples, and the mechanism is that the Seebeck coefficient is nearly zero in the temperature range of 300–420 K and changes its sign at 320 K.